Body height and mass of girls from rural communities in Krosno region as affected by political and economical changes in Poland in the period 1977–1997 - Kosińska, Magdalena (Anthropological Review, 1999)
Body height and mass were determined in girls aged 10.5-18.5 years in three periods: 1977 (n = 1028), 1987 (n = 1255) and in 1997 (n = 1992). The families of those girls were classified into three categories: farmers, farmer-workers and non-farmers. The economical crisis affected predominantly the rural non-farmer population while farmers were most independent from food rationing. After the change of the system and after the state-owned and co-operative farms had been dissolved, the economical situation of the rural non-farmer population worsened further, which showed in the biological parameters of girls.